2021
DOI: 10.1007/s10557-020-07120-8
|View full text |Cite
|
Sign up to set email alerts
|

Promising Therapy for Heart Failure in Patients with Severe COVID-19: Calming the Cytokine Storm

Abstract: The coronavirus disease 19 (COVID-19) pandemic poses a serious global threat to human health and the economy. Based on accumulating evidence, its continuous progression involves not only pulmonary injury but also damage to the cardiovascular system due to intertwined pathophysiological risks. As a point of convergence in the pathophysiologic process between COVID-19 and heart failure (HF), cytokine storm induces the progression of COVID-19 in patients presenting pre-existing or new onset myocardial damage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 158 publications
0
16
0
Order By: Relevance
“…Moreover, the presumptive assumptions of the causative reason for multiple organ damage and mortality during SARS-CoV-2 infection have been closely linked to cytokine storm. Recently, Peng et al (2021) also suggested that the cytokine storm plays a crucial role in the progression of SARS-CoV-2 infection and could be a major reason for multiple organ damage and an increased fatality rate in immunocompromised patients [28].…”
Section: Cytokinesand Chemokines Associated With Cytokine Stormmentioning
confidence: 99%
“…Moreover, the presumptive assumptions of the causative reason for multiple organ damage and mortality during SARS-CoV-2 infection have been closely linked to cytokine storm. Recently, Peng et al (2021) also suggested that the cytokine storm plays a crucial role in the progression of SARS-CoV-2 infection and could be a major reason for multiple organ damage and an increased fatality rate in immunocompromised patients [28].…”
Section: Cytokinesand Chemokines Associated With Cytokine Stormmentioning
confidence: 99%
“…IL-1, TNF-α, and IL-6 have been consistently reported as being central to cytokine storm regulation. A treatment algorithm based on effective inhibition of pro-inflammatory cytokines could be crucial for improving patient outcomes [ 32 ]; for example, Anakinra, a recombinant humanized IL-1 receptor antagonist, has been effectively used to treat MAS [ 33 ]. Recent data have indicated that IL-6 holds a key role in cytokine storm pathophysiology and lung tissue damage, probably by inducing MMP-9 expression in macrophages via Cox-2-dependent and -independent mechanisms [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine storm has a devastating consequence on immune dysregulation in patients ( Fajgenbaum and June 2020 ; Mehta et al, 2020 ). This condition can cause organ failure and increase the fatality rate ( Peng et al, 2021 ). However, several immunotherapeutic molecules are repurposed to treat the cytokine storm among COVID-19 patients.…”
Section: Lessons Learned From Immunotherapeutic Molecules Developmentmentioning
confidence: 99%